Changes in the temporomandibular joint position depending on the sagittal osteotomy technique and extent of mandibular movement. Issue 3 (March 2021) - Möhlhenrich, S.C.; Winterhalder, P.; Ooms, M.; Heitzer, M.; Kilic, K.; Prescher, A.; Hölzle, F.; Danesh, G.; Modabber, A.
Abstract: The bilateral sagittal split osteotomy (BSSO) and high oblique sagittal split osteotomy (HSSO) are common techniques for mandibular movement in orthognathic surgery. The aim of this study was to evaluate the influence of both techniques, as well as movement distances and directions, on the position of the temporomandibular joint (TMJ). A total of 80 mandibular movements were performed on 20 fresh human cadaver heads, four on each head. Pre- and postoperative cone beam computed tomography was used to plan the surgical procedure and analyse the TMJ. Reference measurements included the anterior, superior, and posterior joint spaces, intercondylar distances and angles in the axial and coronal planes, and the sagittal, coronal, and axial angulations of the proximal segment. Only minor differences were found between the BSSO and HSSO techniques, particularly in terms of the intercondylar angle in the axial plane ( P < 0.03) and the condylar angle of the proximal segment in the sagittal plane ( P < 0.011). Observed changes in the TMJ were mostly opposite when moving the mandible forwards and backwards and increased with increasing movement distance. BSSO and HSSO result in similar changes in TMJ position. The extent of the movement distance influences the position of the condyle more than the osteotomy technique.